Thomas Jefferson : 3rd president of the United States - Stefoff, Rebecca, 1951- (Ada, Okla. : Garrett Educational Corp., 1988)
Traces the life of the Virginia politician, American diplomat, and United States president and examines the domestic and foreign issues dominating his career.
Includes index.
Bibliography: p. 117-118.
Keywords: Jefferson, Thomas, -- 1743-1826 -- Juvenile literature; Jefferson, Thomas, -- 1743-1826.; Presidents -- United States -- Biography -- Juvenile literature; Presidents